A estética da loucura na ficção de José Alcides Pinto - Martins Neto, Antonio Maurício (2024)
This research aims to analyze the narrative and temporal dimensions of José Alcides Pinto’s fiction, with a greater emphasis on the novel Entre o sexo: a loucura, a morte, published in 1968, but without being limited to it. The work has a non-linear plot and narration and is rich in figurations about reality, madness, history and time. These four themes, which the study focuses on in more detail, develop in a complex and disorderly fabric. Consequently, the investigation carried out here draws attention to the creative potential of this and other fictions by the author, such as: O Criador de Demônios (1967), Estação da Morte (1968) and Manifesto Traído (1979), demonstrating that they produce temporal experiences and political sensibilities shared in a time and, furthermore, shows that this type of literary text has its own historicity that is not necessarily a reference to “factual” reality. By reading and examining various historical textual sources, we seek to propose a meaning for the literary statement of the writer in question, doing so based on a study of the cited novels, as well as non-literary texts by the author, such as reviews, summaries and interviews. In addition, other texts by different authors are also analyzed, such as columns in cultural magazines, anthologies, literary supplements of newspapers and novels.